Stakeholder engagement in gender and climate change policy processes: Lessons from the climate change, agriculture and food security research program - Mulema, Annet A.; Cramer, Laura K.; Huyer, Sophia (Frontiers Media, 2022)
With the rapid increase in climate shocks and hazards, policies governing climate change have proliferated while the integration of gender considerations to address gender-differentiated needs and impacts has remained a challenge. Stakeholder engagement is touted as a critical ingredient in climate change decisions and governance at different levels to achieve equitable outcomes. However, effective methods and outcomes of gender-responsive stakeholder engagement processes for climate change policy development are rarely published.We apply the framework of 10 principles for effective agricultural research for development programs to analyze the stakeholder engagement processes in the context of the CGIAR's Research Program on Climate Change, Agriculture and Food Security gender and climate change policy projects. We analyze both primary and secondary data to understand the categories of stakeholders engaged, methods of engagement, the outcomes and lessons learned across five regions.Our results show that analysis of the existing policies and programs is a very critical entry point for identifying the points of leverage, the types of stakeholders to engage and how to engage them in the processes that focus on integrating gender in climate policies. Co-learning and co-development of knowledge products cultivate interest and commitment among stakeholders to address gender dynamics, although systematic monitoring and evaluation remains a challenge. This has implications for effective stakeholder engagement in mainstreaming gender in climate policies and evidence-based policy formulation for sustainable agriculture and food systems. Working with influential stakeholders, with the capacity and interest to address gender considerations yields more positive results. Mechanisms to address power relations need to be in place for gender considerations to be voiced and integrated and include women in decision-making processes.